(untitled) (Baghdad Science Journal, 2008)
The interaction between comet Hale-Bopp tail with the solar wind is investigated in the present paper using magneto-hydrodynamic (MHD) numerical simulation, which accounts for the presence of the interplanetary magnetic field (IMF). The simulation is based on three-dimensional Lax-Wendroff explicit scheme, providing second-order accuracy in space and time. The ions produced from the nucleus of the comet will add considerable effects on the microstructure of the solar wind, thus severely altering its physical properties. The present simulation focuses on careful analysis of these properties by means of simulating the behavior of the comet Hale-Bopp’s tail at 1 AU from the sun. These properties include the changes of the plasma density, particle velocity, IMF changes, pressure, and internal energy. The results indicated that comet tail will highly disturb the physical properties of the solar wind for a considerable distance. These changes reflect the effect of including the source term in the present simulation. It is shown that the comet tail will retain its original shape faster as it approaches the sun. Practical comparisons are also presented in the present research with earlier work. The present simulation was made using MATLAB program.